Development of Student Worksheet Based on Contextual Problems to Facilitate Students’ Mathematical Problem-Solving Skills in Flat-Sided Space VIII SMP/MTs - Pratiwi, Aci Ayu; Roza, Yenita; Murni, Atma (FKIP - Universitas Riau, 2025)
This study aims to overcome the problem of minimal use of Student Worksheets (LKPD) based on contextual problems in mathematics learning. Through the 4D development model, the LKPD developed is proven to be valid and practical in facilitating the problem-solving abilities of grade VIII junior high school students on the material of flat-sided solid shapes. The results of the small group LKPD trial obtained a score of 85.11% with a very practical category and the results of the large group LKPD trial obtained a score of 85.70% with a very practical criterion. Thus, overall it is concluded that the LKPD developed based on contextual problems to facilitate students' mathematical problem-solving abilities on the material of flat-sided solid shapes of grade VIII junior high school/MTs has met the valid and practical criteria. Thus, this LKPD has the potential to be an effective alternative in mathematics learning, especially in improving students' critical thinking and problem-solving abilities.